Creepy vs. cool: Switching from human staff to service robots in the hospitality industry. (May 2023) - Kang, Sung-Eun; Koo, Chulmo; Chung, Namho
Abstract: As service robots are becoming more human-looking, people are beginning to perceive robots as creepy in one way but cool in another. This study investigates how the trade-off effects of 'creepiness' and 'coolness' affect the perceived values relating to switching intentions to service robots. The study converged the value-based adoption model (VAM) and push-pull mooring model (PPM) to examine the antecedents of switching intentions and employed a combination of video/scenario-based experimental surveys. Structural analysis of the three groups (e.g., machine-like, semi-human-like, and human-like service robots) revealed that perceived creepiness and perceived coolness both had an impact on perceived value, which, in turn, linked to switching intention from human staff to service robots. Hence, regardless of service types, both negative and positive perceptions co-exist in consumer mindsets. This study provides theoretical and practical implications for three different types of service robots. Highlights: People hold two conflicting perceptions of creepiness and coolness towards service robots. Value-based adoption model and push-pull-mooring model are combined. Perceived value plays a significant mediator in the proposed model. The higher the perceived value of service robots, the more likely it is that consumers will switch to service robots.